First shallow record of Bathyphysa conifera (Studer, 1878) (Siphonophora, Cystonectae), a live specimen in the Strait of Gibraltar. Worldwide species distribution review - MAPSTONE, GILL M.; DIOSDADO, GILBERTO; GUERRERO, ELENA (Mediterranean Marine Science, 2021)
The rarely observed cystonect siphonophore Bathyphysa conifera was recorded for the first time in shallow depth water (- 16 m) as a live specimen, at the entrance to the Mediterranean Sea by SCUBA divers. It is a delicate oceanic species, with earlier records coming mostly from deep water, where it readily adheres to deep sea fishing cables and nets, causing painful stings to fishermen. Deep water sightings from ROVs include in the North Atlantic, off Angola, the Gulf of Mexico, and Monterey Canyon. The present specimen was swimming actively by contracting and expanding its stem, in a yo-yo movement. A review of all reliable records for this species worldwide has been carried out to gain a better knowledge of the present known distribution of this species, both geographical and bathymetric. Bathyphysa conifera may possibly represent an important component of the food web and be perhaps also a competitor to fish in the regions it inhabits.